ENVIRONMENTAL CHARACTER OF PROSPECTIVE TEACHERS IN RIAU PROVINCE - Sri Erlinda (Laboratorium Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Riau, 2023)
This study aims to describe the differences in the character of caring for the environment between student-teacher candidates who have never taken Environmental Education Courses and have never taken them. The population in this study were prospective teacher students at the Faculty of Teaching and Education, University of Riau, totaling 5,013. The research sample used was 640 people spread over 16 study programs. Data collection techniques used were interviews, questionnaires, documentation, and observation. Then, the data were analyzed using different tests and frequency distributions. The results showed that: (1) the character of caring for the environment for prospective teacher students who had not taken Environmental Education Courses was in the medium category; (2) the character of caring for the environment of prospective students who have taken Environmental Education Courses is in the moderate category. The study concludes that there is no difference in the character of caring for the environment for prospective teacher students who have not taken and have taken Environmental Education Courses.